Determinants of Gambling Disorders in Elderly People—A Systematic Review - Guillou Landreat, Morgane; Cholet, Jennyfer; Grall Bronnec, Marie; Lalande, Sophie; Le Reste, Jean Yves (Frontiers in Psychiatry, 2019)
Background: Despite the growth in the number of studies on gambling disorders (GD), Problem gambling in older adults is rarely apparent in literature, despite the potentially severe harm it may cause. Driven by the need to overcome this limitation, a broad systematic review is essential to cover the studies that have already assessed the determinants of GD in the elderly. Objectives: The aim of this systematic review is to understand the determinants related to gambling disorders in elderly people. Methods: A total of 51 studies met the inclusion criteria, and data were synthesised . Results: Three major types of determinants were identified in this review : individual, socio-financial and environmental. Conclusions: This review explored the determinants influencing gambling disorders in older people. The findings are relevant to academic, policymakers, patients and practitioners interested in the identification and prevention of GD in older people.